Molecular Mechanisms of Rett Syndrome: Emphasizing the Roles of Monoamine, Immunity, and Mitochondrial Dysfunction - Julia Lopes Gonçalez; Jenny Shen; Wei Li (Cells)
Rett syndrome (RTT), which predominantly affects females, arises in most cases from mutations in the Methyl-CpG-binding Protein-2 (MECP2) gene. When MeCP2 is impaired, it disrupts the regulation of numerous genes, causing the production of dysfunctional proteins associated with various multi-systemic issues in RTT. In this review, we explore the current insights into molecular signaling related to monoamines, immune response, and mitochondrial function, and their implications for the pathophysiology of RTT. Research has shown that monoamines—such as dopamine, norepinephrine, epinephrine, serotonin, and histamine—exhibit alterations in RTT, contributing to a range of neurological symptoms. Furthermore, the immune system in RTT individuals demonstrates dysfunction through the abnormal activity of microglia, macrophages, lymphocytes, and non-immune cells, leading to the atypical release of inflammatory mediators and disruptions in the NF-κB signaling pathway. Moreover, mitochondria, essential for energy production and calcium storage, also show dysfunction in this condition. The delicate balance of producing and scavenging reactive oxygen species—termed redox balance—is disrupted in RTT. Targeting these molecular pathways presents a promising avenue for developing effective therapies.